Extraction and Characterization of Pectin Obtained from Quince Fruits (Cydonia vulgaris pers) Grown in Turkey - Acikgoz, C. (Asian Journal of Chemistry, 2010)
This paper reports a study of the extraction of pectin from quince (Cydonia vulgaris pers.) at different extracting conditions of temperatures (70, 80 and 90 ºC) and time (60, 90, 120 min) in 0.01 M HCl solutions at pH 2. The pectin content, composition and chemical characterization were studied. Highest yields of 1.83 % (dried pectin g/100 g quince pulp) were obtained at 90 ºC extraction temperature and 90 min extraction time. Galacturonic acid content, the degree of esterification, the gel strength and ash contents in samples were found 77.5, 79.70, 137.50 and 2.47 %, respectively. The higher galacturonic acid and lower ash contents of pectin are two criteria for its purity. The polysaccharides present in the extracts were characterized by FT-IR spectroscopy in the region between 4000-400 cm-1.